A high-strength low-dielectric microwave dielectric ceramic material and preparation method thereof

By adjusting the molar ratio of alumina and silica in microwave dielectric ceramic materials and using high melting point microcrystalline glass powder, combined with cast-lamination technology, the existing materials have both low dielectric constant and high mechanical properties. The problem of this paper achieves an excellent combination of dielectric and mechanical properties, and is suitable for high-temperature co-fired ceramic systems and microwave devices.

CN116924784BActive Publication Date: 2024-12-13SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210342631.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-02
Publication Date
2024-12-13
Estimated Expiration
2042-04-02

AI Technical Summary

Technical Problem

When facing the demand for high frequency and high capacity communication, existing microwave dielectric ceramic materials are difficult to have low dielectric constant, low dielectric loss, excellent mechanical properties and thermal conductivity, especially the dielectric constant of alumina ceramics is relatively large. Facilitate signal transmission.

Method used

High-strength low-intermediate microwave dielectric ceramic material composed of alumina and mullite phases are used to adjust the molar ratio of alumina and silica and use high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 microcrystalline glass powder as sintering The additive realizes the coexistence of the alumina phase and the mullite phase, and combines the cast-laminated process to arrange the sheet alumina in a directional manner to improve the mechanical properties and dielectric properties of the material.

Benefits of technology

The dielectric constant is adjustable between 6.5 and 8.5, the dielectric loss is less than 0.001, the thermal expansion coefficient is 6-8ppm/℃, the thermal conductivity is higher than 5W/m·K, the bending strength is ≥230MPa and the Young's module. The amount is ≥200GPa, suitable for high-temperature co-fired ceramic systems and microwave devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116924784B_ABST
    Figure CN116924784B_ABST
Patent Text Reader

Abstract

The present invention relates to a high-strength low-dielectric microwave dielectric ceramic material and a preparation method thereof. The high-strength low-dielectric microwave dielectric ceramic material comprises: an alumina phase and a mullite phase; the molar ratio of the alumina phase to the mullite phase is 1:(0.1-3); preferably, the alumina phase contains flaky alumina, and the content of the flaky alumina does not exceed 75wt% of the total mass of the microwave dielectric ceramic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-strength low-dielectric microwave dielectric ceramic material, belonging to the field of electronic communications. Background Art

[0002] Information functional ceramic technology is the key technology of the new generation of chip electronic components. In order to adapt to the arrival of the era of integration of various electronic devices, electronic devices have put forward higher requirements for the development of circuits towards miniaturization, high density, multifunctionality, high reliability, high speed and high power. This has posed challenges to information functional ceramics while also providing good development opportunities. With the increasingly rapid development of microwave communication technology, some equipment used in microwave communication (such as high-frequency substrates, antennas, resonators and filters, etc.) require microwave dielectric ceramics to have a low relative dielectric constant (ε r <10)、small dielectric loss (tanδ<10 -3 ) and the near-zero resonant frequency temperature coefficient (τ f ≈0), this is because the signal delay of microwave dielectric materials is proportional to the dielectric constant εr. In order to reduce the delay, people have paid more and more attention to some microwave dielectric materials with smaller εr and lower loss in recent years.

[0003] However, with the continuous increase in communication frequency and capacity, in addition to requiring ceramic materials to have excellent dielectric properties, they also need excellent mechanical and thermal properties to cope with problems such as temperature shock and high-intensity vibration in harsh working environments. Although except for alumina ceramics, which have excellent dielectric properties, mechanical properties and thermal conductivity, other low-dielectric ceramics do not have the above advantages. However, the dielectric constant of alumina ceramics is relatively large, which is not conducive to signal transmission. Therefore, the development of new microwave dielectric ceramics with low dielectric, high mechanical strength and thermal conductivity is one of the important directions in the field of microwave dielectric materials. Summary of the invention

[0004] In order to solve the above technical problems, the present invention discloses a high-strength and low-dielectric microwave dielectric ceramic material and a preparation method thereof. The material has low-dielectric adjustable dielectric properties, excellent mechanical properties and thermal conductivity.

[0005] On the one hand, the present invention provides a high-strength, low-dielectric microwave dielectric ceramic material, which comprises: an alumina phase and a mullite phase; the molar ratio of the alumina phase to the mullite phase is 1:(0.1-3); preferably, the alumina phase contains flaky alumina, and the content of the flaky alumina does not exceed 75wt% of the total mass of the microwave dielectric ceramic material.

[0006] Preferably, the relative density of the microwave dielectric ceramic material is 98-99.5%; the dielectric constant of the microwave dielectric ceramic material is adjustable between 6.5 and 8.5, and the dielectric loss is <0.001; the thermal expansion coefficient of the microwave dielectric ceramic material is 5-8ppm / °C, and the thermal conductivity is >5W / m·K; the bending strength of the microwave dielectric ceramic material is ≥230MPa, and the Young's modulus is ≥200GPa.

[0007] On the other hand, the present invention provides a method for preparing a high-strength, low-dielectric microwave dielectric ceramic material, which uses Al2O3 ceramic powder and SiO2 ceramic powder as raw materials, and performs in-situ sintering under the action of a sintering aid to obtain a high-strength, low-dielectric microwave dielectric ceramic material in which an alumina phase and a mullite phase coexist; preferably, the sintering aid contains a high-melting point Ln2O3-RO-SiO2-B2O3-Al2O3 microcrystalline glass powder, and the amount of the high-melting point Ln2O3-RO-SiO2-B2O3-Al2O3 microcrystalline glass powder added does not exceed 10wt% of the total mass of the raw materials.

[0008] Preferably, the Al2O3 ceramic powder is irregularly shaped alumina powder with a particle size of 0.3 to 5 μm or / and flaky alumina powder with a diameter of 1 to 30 μm and a thickness of more than 100 nm;

[0009] The SiO2 ceramic powder is SiO2 powder with a particle size of 0.2 to 5 μm (preferably 0.5 to 5 μm); the molar ratio of the Al2O3 ceramic powder to the SiO2 ceramic powder is in the range of 3:(0.1 to 1.9).

[0010] Preferably, the mass ratio of irregular alumina powder Al2O3 to flaky alumina powder in the Al2O3 ceramic powder is in the range of 1:(0-5). In the present invention, flaky alumina has poor sintering activity and generally does not participate in the reaction. By adopting the above mass ratio, it is possible to ensure that there is enough alumina powder to form the mullite phase while retaining the presence and directional arrangement of flaky alumina to improve the mechanical properties of the material.

[0011] Preferably, the composition of the high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 glass-ceramics is Ln2O3-RO-SiO2-B2O3-Al2O3, wherein Ln=at least one of Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Cd, Tb, Dy, Ho, Er, Tm, Yb, Lu, R=at least one of Ca, Ba, Sr, and the glass components are 0-10 mol% Ln2O3, 10-30 mol% RO, 25-5 0mol% SiO2, 0-5mol% B2O3, 10-30mol% Al2O3; preferably, the crystalline phases precipitated in the melting point Ln2O3-RO-SiO2-B2O3-Al2O3 glass-ceramics include one or more phases of mullite, barium silicate (BaSiO3 or / and BaSi2O5), and calcium silicate (CaSiO3 or / and CaSi2O5); the particle size of the high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 glass-ceramics powder is D 90 <2μm, the addition amount is 3~7wt%. In the present invention, a high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 microcrystalline glass powder with a specific content and a specific composition is selected as a sintering aid. Since the composition of the sintering aid is the same as that of the mullite phase, it can not only assist the mass transfer of the glass liquid phase to play a role in rapid sintering, but also precipitate the same mullite crystal phase without other impurities, thereby achieving the sintering density of the composite microwave dielectric ceramic material with the coexistence of the Al2O3 phase and the mullite phase.

[0012] Preferably, the sintering aid further comprises a second aid powder; the second aid powder comprises at least one of MgO, Y2O3, ZrO2, AlF3, and CaF2, and the amount of the second aid added does not exceed 5wt% of the total mass of the raw materials; the particle size D of the second aid powder is 90 <2μm.

[0013] Preferably, the method comprises the following steps:

[0014] (1) Al2O3 ceramic powder, SiO2 ceramic powder, sintering aid, and solvent are mixed, and then a binder, a dispersant, and a plasticizer are added to obtain a mixed slurry, wherein the viscosity of the mixed slurry is preferably 4 to 8 KPa·S;

[0015] (2) filtering and vacuum degassing the obtained mixed slurry, and then performing tape casting using a tape casting device to obtain a raw tape; preferably, the tape casting device is set to a drying temperature of 40 to 60° C.;

[0016] (3) The obtained raw tape is cut and stacked, and then hot isostatically pressed and in-situ sintered to obtain a high-strength low-dielectric microwave dielectric ceramic material.

[0017] Preferably, the in-situ sintering system includes: continuously heating up to 1550-1650°C at a heating rate of 3-10°C / min, keeping the temperature for 3-6 hours, and then cooling down to below 1000°C at a cooling rate of 2-5°C / min.

[0018] Preferably, before in-situ sintering, the temperature is raised to 250-350°C at a rate of 0.5-2°C / min and kept at that temperature for 2-4 hours, and then raised to 450-550°C at a rate of 0.5-2°C / min and kept at that temperature for 2-4 hours to fully remove organic matter.

[0019] Beneficial effects of the present invention:

[0020] This high-temperature substrate ceramic material has excellent dielectric, thermal and mechanical properties, with a dielectric constant adjustable between 7 and 8.5, a dielectric loss lower than 0.001, a thermal expansion coefficient of 6 to 8 ppm / ℃, a thermal conductivity higher than 5W / m·K, a flexural strength ≥300MPa, and a Young's modulus ≥200GPa. It has excellent co-firing matching with tungsten slurry and is a high-temperature co-fired ceramic material with great potential application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the SEM image of the raw material alumina. It can be seen from the image that the particle size of the alumina powder is between 300 and 1000 nm.

[0022] Figure 2 This is the SEM image of raw silicon dioxide, from which we can see that the particle size of silicon dioxide powder is between 200 and 800 nm;

[0023] Figure 3 The SEM image of the raw material flaky aluminum oxide shows that the size of the selected flaky aluminum oxide powder is 300-2000nm thick and 1-30μm in diameter;

[0024] Figure 4 : The XRD spectra of the ceramic materials corresponding to Examples 1-2 and 6-8. It can be seen from the figure that the composite microwave dielectric ceramic material in which the alumina phase and the mullite phase coexist is obtained by the in-situ synthesis method of the sintering aid, and as the molar ratio of alumina to silica changes, the molar ratio of alumina to mullite phase also changes, indicating that the alumina and mullite phase components in the composite ceramic material can be regulated by adjusting the composition of alumina and silica, thereby achieving adjustable dielectric properties;

[0025] Figure 5: is the XRD spectrum of the ceramic material corresponding to Comparative Example 1. It can be seen from the figure that the obtained phase is a composite of aluminum oxide and silicon dioxide phases, indicating that the mullite phase cannot be obtained without adding a sintering aid. Therefore, a suitable sintering aid is required to promote in-situ sintering to obtain a microwave dielectric ceramic composite of aluminum oxide phase and mullite phase;

[0026] Figure 6 This is a SEM image of the sample of Example 1. It can be seen from the image that a sintered high-density ceramic material is obtained in Example 1;

[0027] Figure 7 This is a SEM image of the sample of Example 2. It can be seen from the image that a sintered high-density ceramic material is obtained in Example 2;

[0028] Figure 8 This is a SEM image of the sample of Example 5, from which it can be seen that a sintered high-density ceramic material is obtained in Example 5;

[0029] Fig. 9 This is the SEM image of the sample of Example 6. It can be seen from the figure that the oriented Al2O3 and Al6Si2O 13 Bionic composite ceramic materials, showing that the oriented arrangement of alumina sheets can be achieved through the tape casting-lamination method, thereby improving their mechanical properties;

[0030] Fig.10 This is the SEM image of the sample of Example 7. It can be seen from the figure that the oriented Al2O3 and Al6Si2O 13 Bionic composite ceramic materials, showing that the oriented arrangement of alumina sheets can be achieved through the tape casting-lamination method, thereby improving their mechanical properties;

[0031] Fig.11 This is the SEM image of the sample of Example 8. It can be seen from the figure that the oriented Al2O3 and Al6Si2O 13 Bionic composite ceramic materials, showing that the oriented arrangement of alumina sheets can be achieved through the tape casting-lamination method, thereby improving their mechanical properties;

[0032] Fig.12 The SEM image of the sample of Comparative Example 7 shows that when no sintering aid is added, a large number of 5-20 um pores are present in the microstructure of the composite ceramic, and the crystal phase is arranged irregularly, indicating that in the absence of a sintering aid, a dense composite ceramic material cannot be obtained by the in-situ sintering method at 1600°C;

[0033] Fig.13This is the SEM image of the sample of comparative example 8. It can be seen from the image that the sample has many pores and stratification occurs, which means that if the sintering aid is not selected properly, the sample will not be sintered densely and will not achieve the purpose of improving the mechanical properties. DETAILED DESCRIPTION

[0034] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0035] In the present invention, the microwave dielectric ceramic material is a composite ceramic material in which an alumina phase and a mullite phase coexist by in-situ sintering using Al2O3 ceramic powder and SiO2 ceramic powder as raw materials under the action of a sintering aid.

[0036] In the present invention, the molar ratio of alumina powder and silica powder in the composite material and the sintering aid are adjusted to achieve Al2O3 / Al6Si2O 13 The comprehensive excellent performance control of composite microwave dielectric ceramic materials: the dielectric constant is adjustable between 6.5 and 8.5, the dielectric loss is lower than 0.001, the thermal expansion coefficient is 6 to 8 ppm / ℃, the thermal conductivity is higher than 5W / m·K, the flexural strength is ≥230MPa, and the Young's modulus is ≥100GPa.

[0037] In the present invention, the raw materials include: alumina powders of different morphologies: irregularly shaped alumina powders with a particle size of 0.3 to 5 μm, flaky alumina powders with a diameter of 1 to 30 μm and a thickness of >100 nm; SiO2 powders with a particle size of 0.5 to 5 μm, and high-melting-point microcrystalline glass powders as sintering aids, the content of which can be 0 to 10 wt% of the total mass of Al2O3 ceramic powder and SiO2 ceramic powder. Preferably, irregularly shaped alumina powders with a particle size of 0.3 to 3 μm, SiO2 powders with a particle size of 0.5 to 3 μm, and 3 to 7 wt% sintering aids. The molar ratio of alumina powder to silica powder in the raw materials can be 3:(0.1 to 1.9). More preferably, the mass ratio of irregularly shaped alumina powders to flaky alumina powders in alumina powders can be 1:(0 to 5).

[0038] In an optional embodiment, the sintering aid includes a high melting point glass-ceramic powder, whose composition may be aLn2O3-bRO-cSiO2-dB2O3-eAl2O3 (Ln = Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Cd, Tb, Dy, Ho, Er, Tm, Yb, Lu, R = Ca, Ba, Sr), a = 0 to 10, b = 10 to 30, c = 25 to 50, d = 0 to 5, e = 10 to 30, and a + b + c + d + e = 100. The precipitated crystalline phases in the glass-ceramic include one or more of mullite phase, barium silicate phase (BaSiO3, BaSi2O5), and calcium silicate phase (CaSiO3 or / and CaSi2O5). The particle size of the high melting point glass-ceramic powder may be D 90 <2μm. The addition amount of high melting point glass-ceramics can be 3-7wt%.

[0039] More preferably, the sintering aid further comprises a second aid powder of at least one of MgO, Y2O3, ZrO2, and ZrSiO4. The particle size D of the second aid powder 90 <2um, the added amount can be 0~5wt%.

[0040] The following is an exemplary description of a method for preparing a microwave dielectric ceramic material.

[0041] Preparation of Ln2O3-RO-SiO2-B2O3-Al2O3 glass powder. Mix Ln source, R source, Al source, B source and Si source in a molar ratio of ((0-10):(10-30):(10-30):(0-5):(25-50) to obtain a raw material mixture A; melt the raw material mixture A and quench it to obtain glass fragments; and ball-mill and sand-mill the glass fragments, dry and sieve them to obtain the glass powder. In the process of preparing Ln2O3-RO-SiO2-B2O3-Al2O3 glass powder, the Ln source can be one or more Ln2O3 with a purity greater than 99%, and the R source can be R with a purity greater than 99%. CO3, R(NO3)2 and RCl2, the Al source can be one or more of Al2O3 and Al(OH)3 with a purity greater than 99%, the B source can be H3BO3 with a purity greater than 99%, and the Si source can be SiO2 with a purity greater than 99%. The use of raw materials with a purity greater than 99% to prepare Ln2O3-RO-SiO2-B2O3-Al2O3 glass powder can ensure the stability of the glass crystallization phase and reduce the influence of impurities on dielectric properties. The temperature of the glass melting can be 1500-1650°C and the time can be 1.5-4 hours.

[0042] Alumina powder, flaky alumina powder, silica powder, glass powder and other sintering aids are mixed in a certain mass ratio and dried to obtain a mixed material.

[0043] The mixed material powder is evenly mixed with a binder, a dispersant, a plasticizer, and an organic solvent by planetary ball milling to obtain a high-viscosity casting slurry (4-8KPa·S). The ball milling process for preparing microwave dielectric ceramics can be divided into two steps. The first step can be to mix the powder, solvent and dispersant evenly and ball mill for 1-3 hours at a speed of 300-500 rpm, and the second step is to add a binder and a plasticizer and ball mill for 1-3 hours at a speed of 450-550 rpm. The solid content of the mixed slurry can be 60-70wt%. The organic solvent in the mixed slurry can be a mixed solvent of alcohols and benzene, and the content can be 25-30wt%. The binder in the mixed slurry can be a polyvinyl butyral binder, and the content can be 7-10wt%. The dispersant in the mixed slurry can be a BYK system and a fish oil dispersant, and the content can be 0.5-2wt%. The plasticizer in the mixed slurry may be dioctyl phthalate, and the content may be 1-3 wt %

[0044] The raw tape is cut and laminated, and then hot isostatically pressed into a green body, and the binder removal-sintering process is performed to obtain high-strength and low-intermediate Al2O3 / Al6Si2O 13 Composite microwave dielectric ceramic material. During the tape casting process, the bottom mold moves at a speed of 0.2 to 0.4 m / min, and the slurry thickness can be controlled to 50 to 200 μm by a scraper. The parameters of the hot isostatic pressing include: the pressure can be 20 to 40 MPa, and the temperature can be 50 to 80°C. The sintering process can be to continue heating to 1550 to 1650°C at a heating rate of 3 to 10°C / min, keep warm for 3 to 6 hours, and then cool down to below 1000°C at a cooling rate of 2 to 5°C / min.

[0045] Preferably, debinding is performed before sintering. The debinding process may be heating the temperature to 250-350°C at a rate of 0.5-2°C / min and keeping the temperature for 2-4 hours, and then heating the temperature to 450-550°C at a rate of 0.5-2°C / min and keeping the temperature for 2-4 hours to fully remove organic matter.

[0046] In the present invention, the rapid chemical reaction of alumina and silicon dioxide is achieved by mass transfer between glass and ceramic liquid phase to produce Al6Si2O 13 phase, and at the same time inhibit the problem of poor density of the material due to volume expansion during the synthesis of mullite, ① thereby improving the mechanical properties of the composite ceramic (bending strength 100-200MPa), and at the same time according to the microwave dielectric properties of the composite material (Al2O3 ceramics: εr = 9.8, tanδ < 1×10 -4 , Al6Si2O13 ceramics: εr = 6.5, tanδ < 5 × 10 -4) The mixing rule can make the dielectric constant of the obtained composite material adjustable and lower than 10 and the dielectric loss low; on the other hand, the oriented arrangement of the flaky aluminum oxide is achieved by the tape casting-lamination method to obtain a new type of bionic microwave dielectric ceramic material that imitates the pearl layer, and ② further improve the mechanical properties (bending strength 230-500MPa). Specifically, in the present invention, the prepared raw ceramic powder and sintering aid are mixed according to the mass ratio, tape casting-laminated molding, and sintered at 1500-1650°C to form a microwave dielectric ceramic material. In the present invention, the microwave dielectric properties, mechanical properties and thermal properties of the microwave dielectric ceramic material can be adjusted by adjusting the molar ratio of alumina to silica, the mass ratio of irregular alumina to flaky alumina, and the tape casting oriented arrangement process: the dielectric constant is adjustable between 6.5 and 8.5, and the dielectric loss tanδ is <5×10 -3 , thermal expansion coefficient 5 ~ 8ppm / ℃, thermal conductivity higher than 5W / m K, flexural strength ≥ 230MPa, Young's modulus ≥ 200GPa, and the preparation process is simple, pollution-free, low cost, can be used for the manufacture of high-temperature co-fired ceramic systems, multilayer dielectric resonators, microwave antennas, filters and other microwave devices. It is a low-temperature co-fired ceramic material with great potential application value.

[0047] In the present invention,

[0048] (1) Performance characterization: The thermal expansion coefficient of the obtained ceramic material was tested using a thermal expansion instrument. The bending strength and Young's modulus of the obtained ceramic material were tested using a 5566 universal testing machine. The thermal conductivity of the obtained ceramic material was tested using a laser thermal conductivity meter. The phase and morphology of the ceramic material were measured using a high-resolution powder X-ray diffractometer and a field emission scanning electron microscope.

[0049] (2) Microwave dielectric properties: The plate method was used to measure the relative dielectric constant εr and dielectric loss tan quality factor Q×f of the sample at microwave frequency. The instrument used was Agilent E8362B vector network analyzer, and the test sample size was 10×10×0.9 mm.

[0050] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0051] Example 1

[0052] (1) According to the glass ratio of 2.47La2O3-17.92BaO-41.15SiO2-7.69B2O3-30.77Al2O3 (100 mol%), weigh 73.74 g of lanthanum oxide, 324.39 g of barium carbonate, 287.84 g of aluminum oxide, 87.19 g of boric acid, and 226.84 g of silicon dioxide, pour the prepared materials into a mortar, add an appropriate amount of deionized water, stir evenly, and place in a platinum crucible at 1575°C for 2 h, then pour the molten glass directly into deionized water for quenching to obtain a glass sample;

[0053] (2) 1000 g of glass fragments obtained in step (1) + 3600 g of zirconium oxide balls + 600 mL of anhydrous ethanol were placed in an alumina ceramic jar and milled in a planetary ball mill at a speed of 450 rpm for 2 h. The slurry was passed through a 120-mesh sieve;

[0054] (3) placing the glass powder slurry ball-milled in step (2) in a sand mill and grinding at a speed of 2000 rpm for 3 h, and then passing the slurry through a 400-mesh sieve and placing it in a 110° C. constant temperature drying oven for 12 h to obtain glass powder (particle size D90≈2±0.5 μm) for later use;

[0055] (4) According to the ratio in Table 1, 181.1 g of alumina powder, 8.9 g of silicon oxide powder, and 10 g of glass powder were weighed, 200 g of the material + 300 g of zirconium oxide balls + 100 mL of anhydrous ethanol were added to a polyethylene tetrachloride tank, and the mixture was milled in a planetary ball mill at a speed of 450 rpm for 1 h. After drying, the mixture was passed through a 100-mesh sieve to obtain a uniformly mixed powder;

[0056] (5) 200 g of the powder was first placed in a nylon jar together with 20 g of anhydrous ethanol, 20 g of xylene and 2 g of BYK-255 dispersant, and the mixture was subjected to planetary milling at a speed of 450 rpm for 1 hour. Then, 14 g of PVB 98 binder and 6.8 g of S160 plasticizer were added and the mixture was subjected to planetary milling at a speed of 300 rpm for 1 hour to obtain a casting slurry;

[0057] (6) filtering the casting slurry and the grinding balls through a 100-mesh sieve and performing vacuum degassing treatment;

[0058] (7) The slurry is poured onto the PCB bottom mold for casting, and is driven forward by the PCB bottom mold at a speed of 0.25 m / min. The slurry thickness is controlled at 100 μm by a scraper, and the temperature in the casting chamber is controlled at 65°C. After the slurry is formed into a film tape, the bottom mold is removed to obtain a green body (green ceramic sheet);

[0059] (8) The blank was simply cut according to the XY axis shrinkage rate of 14.5% and the Z axis shrinkage rate of 30%. The samples for dielectric performance test were cut, laminated and hot isostatically pressed according to the size of 12×12×1.2 mm, the samples for mechanical performance test were cut, laminated and hot isostatically pressed according to the size of 42×42×4 mm, and the samples for thermal conductivity test were cut, laminated and hot isostatically pressed according to the size of 10×10×2.8 mm, wherein the hot isostatic pressing pressure was controlled at 35 MPa, the temperature was 80° C., and the holding time was 30 minutes;

[0060] (9) The sample was placed in a muffle furnace and heated to 300 °C at a rate of 1 °C / min and kept at that temperature for 4 hours. The sample was then heated to 500 °C at a rate of 1 °C / min and kept at that temperature for 2 hours to fully remove organic matter. The sample was then heated to 1550 °C at a rate of 5 °C / min and kept at that temperature for 4 hours to sinter. The sample was then cooled to below 1000 °C at a rate of 1 °C / min.

[0061] Example 2

[0062] The sealing component preparation process in this Example 2 refers to that in Example 1, except that: 173 g of aluminum oxide powder, 16.98 g of silicon oxide powder, and 10 g of glass powder.

[0063] Example 3

[0064] The sealing component preparation process in this Example 3 refers to that in Example 1, except that: 181.1 g of aluminum oxide powder, 8.9 g of silicon oxide powder, and 14 g of glass powder.

[0065] Example 4

[0066] The sealing component preparation process in this Example 4 refers to that in Example 1, except that: 173 g of aluminum oxide powder, 16.98 g of silicon oxide powder, and 14 g of glass powder.

[0067] Example 5

[0068] The sealing component preparation process in this Example 5 refers to that in Example 1, except that: 165.6 g of aluminum oxide powder, 24.4 g of silicon oxide powder, and 14 g of glass powder.

[0069] Table 1 shows the composition and performance parameters of the high-strength low-dielectric microwave dielectric ceramic materials prepared in Examples 1-5:

[0070]

[0071] Example 6

[0072] The sealing component preparation process in this Example 6 refers to that in Example 1, except that: 90.55 g of aluminum oxide powder, 90.55 g of flaky aluminum oxide, 8.9 g of silicon oxide powder, and 10 g of glass powder.

[0073] Example 7

[0074] The sealing component preparation process in this Example 7 refers to that in Example 1, except that: 86.5 g of aluminum oxide powder, 86.5 g of flaky aluminum oxide, 16.98 g of silicon oxide powder, and 10 g of glass powder.

[0075] Example 8

[0076] The sealing component preparation process in this Example 8 refers to that in Example 1, except that: 82.8 g of aluminum oxide powder, 82.8 g of flaky aluminum oxide, 24.4 g of silicon oxide powder, and 10 g of glass powder.

[0077] Example 9

[0078] The sealing component preparation process in this Example 9 refers to that in Example 1, except that: 79.4 g of aluminum oxide powder, 79.4 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 10 g of glass powder.

[0079] Example 10

[0080] The sealing component preparation process in this Example 10 refers to that in Example 1, except that: 76.28 g of aluminum oxide powder, 76.28 g of flaky aluminum oxide, 37.44 g of silicon oxide powder, and 10 g of glass powder.

[0081] Table 2 shows the composition and performance parameters of the high-strength low-dielectric microwave dielectric ceramic materials prepared in Examples 6-10:

[0082]

[0083]

[0084] Embodiment 11

[0085] The sealing component preparation process in this Example 11 refers to that in Example 1, except that: 73.38 g of aluminum oxide powder, 73.38 g of flaky aluminum oxide, 43.24 g of silicon oxide powder, and 10 g of glass powder.

[0086] Example 12

[0087] The sealing component preparation process in this Example 12 refers to that in Example 9, except for: 79.4 g of aluminum oxide powder, 79.4 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 14 g of glass powder.

[0088] Example 13

[0089] The sealing component preparation process in this Example 13 refers to that in Example 9, except for: 79.4 g of aluminum oxide powder, 79.4 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, 6 g of glass powder and 8 g of zirconium oxide.

[0090] Embodiment 14

[0091] The sealing component preparation process in this Example 14 refers to that in Example 9, except that: 105.87 g of aluminum oxide powder, 52.93 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 10 g of glass powder.

[0092] Embodiment 15

[0093] The sealing component preparation process in this Example 15 refers to that in Example 9, except that: 52.93 g of aluminum oxide powder, 105.87 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 10 g of glass powder.

[0094] Table 3 shows the composition and performance parameters of the high-strength low-dielectric microwave dielectric ceramic materials prepared in Examples 11-15:

[0095]

[0096]

[0097] Example 16

[0098] The sealing component preparation process in this Example 16 refers to that in Example 9, except that: 119.005 g of aluminum oxide powder, 39.685 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 10 g of glass powder.

[0099] Embodiment 17

[0100] The sealing component preparation process in this Example 17 refers to that in Example 9, except that: 132.28 g of aluminum oxide powder, 26.46 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 10 g of glass powder.

[0101] Embodiment 18

[0102] The sealing component preparation process in this Example 18 refers to that in Example 9, except that: 142.866 g of aluminum oxide powder, 15.874 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 10 g of glass powder.

[0103] Embodiment 19

[0104] The sealing component preparation process in this Example 19 refers to that in Example 9, except that: 142.866 g of aluminum oxide powder, 15.874 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 18 g of glass powder.

[0105] Embodiment 20

[0106] The sealing component preparation process in this Example 20 refers to that in Example 9, except that: 142.866 g of aluminum oxide powder, 15.874 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 20 g of glass powder.

[0107] Embodiment 21

[0108] The sealing component preparation process in this Example 21 refers to that in Example 9, except that: the glass powder is prepared according to 3.5Sm2O3-1.5CaO-25BaO-40SiO2-5B2O3-25Al2O3 glass.

[0109] Table 4 shows the composition and performance parameters of the high-strength low-dielectric microwave dielectric ceramic materials prepared in Examples 16-21:

[0110]

[0111]

[0112] Comparative Example 1

[0113] According to the proportion in Table 1, 143.58g of alumina powder and 56.42g of silica powder, 200g of the material + 300g of zirconium oxide balls + 100mL of anhydrous ethanol were added into a polyethylene tetrachloride tank, and ball milled for 1h in a planetary ball mill at a speed of 450 rpm. After drying, the mixture was passed through a 100-mesh sieve to obtain a uniformly mixed powder;

[0114] (2) 200 g of the powder was first placed in a nylon jar together with 20 g of anhydrous ethanol, 20 g of xylene and 2 g of BYK-255 dispersant, and subjected to planetary milling at a speed of 450 rpm for 1 hour, and then 14 g of PVB 98 binder and 6.8 g of S160 plasticizer were added and subjected to planetary milling at a speed of 300 rpm for 1 hour to obtain a casting slurry;

[0115] (3) filtering the casting slurry and the grinding balls through a 100-mesh sieve and performing vacuum degassing treatment;

[0116] (4) The slurry is poured onto the PCB bottom mold for casting, and is driven forward by the PCB bottom mold at a speed of 0.25 m / min. The slurry thickness is controlled at 100 μm by a scraper, and the temperature in the casting chamber is controlled at 65°C. After the slurry is formed into a film tape, the bottom mold is removed to obtain a green body (green ceramic sheet);

[0117] (5) The blank was simply cut according to the XY axis shrinkage rate of 14.5% and the Z axis shrinkage rate of 30%. The samples for dielectric performance test were cut, laminated and hot isostatically pressed according to the size of 12×12×1.2 mm, the samples for mechanical performance test were cut, laminated and hot isostatically pressed according to the size of 42×42×4 mm, and the samples for thermal conductivity test were cut, laminated and hot isostatically pressed according to the size of 10×10×2.8 mm, wherein the hot isostatic pressing pressure was controlled at 35 MPa, the temperature was 80°C, and the holding time was 30 minutes;

[0118] (6) Place the sample in a muffle furnace and heat it to 300 °C at a rate of 1 °C / min and keep it at that temperature for 4 hours. Then heat it to 500 °C at a rate of 1 °C / min and keep it at that temperature for 2 hours to fully remove organic matter. Then heat it to 1600 °C at a rate of 5 °C / min and keep it at that temperature for 4 hours to sinter. Then cool it down to below 1000 °C at a rate of 1 °C / min.

[0119] Comparative Example 2

[0120] (1) According to the glass ratio of La2O3-BaO-SiO2-B2O3-Al2O3 (mol%), weigh 23.74 g of lanthanum oxide, 374.39 g of barium carbonate, 287.84 g of aluminum oxide, 87.19 g of boric acid, and 226.84 g of silicon dioxide. Pour the prepared materials into a mortar, add an appropriate amount of deionized water, stir evenly, and place in a platinum crucible at 1575°C for 2 h. Then, pour the molten glass directly into deionized water for quenching to obtain a glass sample.

[0121] (2) 1000 g of glass fragments obtained in step (1) + 3600 g of zirconium oxide balls + 600 mL of anhydrous ethanol were placed in an alumina ceramic jar and milled in a planetary ball mill at a speed of 450 rpm for 2 h. The slurry was passed through a 120-mesh sieve;

[0122] (3) placing the glass powder slurry ball-milled in step (2) in a sand mill and grinding at a speed of 2000 rpm for 3 h, and then passing the slurry through a 400-mesh sieve and placing it in a 110° C. constant temperature drying oven for 12 h to obtain glass powder (particle size D90≈2±0.5 μm) for later use;

[0123] (4) According to the ratio in Table 1, 158.8 g of alumina powder, 31.2 g of silicon oxide powder, and 10 g of glass powder were weighed, 200 g of the material + 300 g of zirconium oxide balls + 100 mL of anhydrous ethanol were added to a polyethylene tetrachloride tank, and the mixture was ball milled in a planetary ball mill at a speed of 450 rpm for 1 h. After drying, the mixture was passed through a 100-mesh sieve to obtain a uniformly mixed powder;

[0124] (5) 200 g of the powder was first placed in a nylon jar together with 20 g of anhydrous ethanol, 20 g of xylene and 2 g of BYK-255 dispersant, and the mixture was subjected to planetary milling at a speed of 450 rpm for 1 hour. Then, 14 g of PVB 98 binder and 6.8 g of S160 plasticizer were added and the mixture was subjected to planetary milling at a speed of 300 rpm for 1 hour to obtain a casting slurry;

[0125] (6) filtering the casting slurry and the grinding balls through a 100-mesh sieve and performing vacuum degassing treatment;

[0126] (7) The slurry is poured onto the PCB bottom mold for casting, and is driven forward by the PCB bottom mold at a speed of 0.25 m / min. The slurry thickness is controlled at 100 μm by a scraper, and the temperature in the casting chamber is controlled at 65°C. After the slurry is formed into a film tape, the bottom mold is removed to obtain a green body (green ceramic sheet);

[0127] (8) The blank was simply cut according to the XY axis shrinkage rate of 14.5% and the Z axis shrinkage rate of 30%. The samples for dielectric performance test were cut, laminated and hot isostatically pressed according to the size of 12×12×1.2 mm, the samples for mechanical performance test were cut, laminated and hot isostatically pressed according to the size of 42×42×4 mm, and the samples for thermal conductivity test were cut, laminated and hot isostatically pressed according to the size of 10×10×2.8 mm, wherein the hot isostatic pressing pressure was controlled at 35 MPa, the temperature was 80° C., and the holding time was 30 minutes;

[0128] (9) The sample was placed in a muffle furnace and heated to 300 °C at a rate of 1 °C / min and kept at that temperature for 4 hours. The sample was then heated to 500 °C at a rate of 1 °C / min and kept at that temperature for 2 hours to fully remove organic matter. The sample was then heated to 1550 °C at a rate of 5 °C / min and kept at that temperature for 4 hours to sinter. The sample was then cooled to below 1000 °C at a rate of 1 °C / min.

[0129] Comparative Example 3

[0130] The sealing component preparation process in Comparative Example 3 refers to Comparative Example 2, except that: 152.56 g of aluminum oxide powder, 37.44 g of silicon oxide powder, and 10 g of glass powder.

[0131] Comparative Example 4

[0132] The sealing component preparation process in Comparative Example 4 refers to Comparative Example 2, except that: 146.76 g of aluminum oxide powder, 43.24 g of silicon oxide powder, and 10 g of glass powder.

[0133] Comparative Example 5

[0134] The sealing component preparation process in Comparative Example 5 refers to Comparative Example 2, except that: 158.8 g of aluminum oxide powder, 31.2 g of silicon oxide powder, and 14 g of glass powder.

[0135] Comparative Example 6

[0136] The sealing component preparation process in Comparative Example 6 refers to that in Example 1, except that: 79.4 g of aluminum oxide powder, 79.4 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 25 g of glass powder.

[0137] Comparative Example 7

[0138] The sealing component preparation process in this comparative example 7 refers to that in Example 1, except that: 79.4 g of aluminum oxide powder, 79.4 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 0 g of glass powder.

[0139] Comparative Example 8

[0140] The sealing component preparation process in this comparative example 8 refers to that in Example 1, except that: 79.4 g of aluminum oxide powder, 79.4 g of flaky aluminum oxide, 31.2 g of silicon oxide powder, and 10 g of glass powder; and the glass powder composition is 0La2O3-0BaO-90SiO2-5B2O3-5Al2O3 glass ratio (100 mol%).

[0141] Table 3 shows the composition and performance parameters of the high-strength low-dielectric microwave dielectric ceramic materials prepared in Comparative Examples 1-7:

[0142]

[0143]

Claims

1. A high-strength low-dielectric microwave dielectric ceramic material, characterized in that: The microwave dielectric ceramic material comprises: an alumina phase and a mullite phase; the molar ratio of the alumina phase to the mullite phase is 1:(0.1-3); the alumina phase contains flaky alumina, and the content of the flaky alumina does not exceed 75wt% of the total mass of the microwave dielectric ceramic material; The preparation method of the high-strength low-dielectric microwave dielectric ceramic material comprises: mixing Al2O3 ceramic powder, SiO2 ceramic powder and sintering aid to prepare a mixed slurry, and performing tape casting, lamination and in-situ sintering to obtain a high-strength low-dielectric microwave dielectric ceramic material in which an alumina phase and a mullite phase coexist; wherein, The Al2O3 ceramic powder comprises: irregularly shaped alumina powder with a particle size of 0.3 to 5 μm and flaky alumina powder with a diameter of 1 to 30 μm and a thickness of more than 100 nm; the mass ratio of the irregularly shaped alumina powder to the flaky alumina powder in the Al2O3 ceramic powder is in the range of 1:(0.1 to 5); The molar ratio of the Al2O3 ceramic powder to the SiO2 ceramic powder is in the range of 3:(0.1-1.9); The in-situ sintering system includes: heating to 1550-1650° C. at a heating rate of 3-10° C. / min, keeping the temperature for 3-6 hours, sintering, and then cooling to below 1000° C. at a cooling rate of 2-5° C. / min.

2. The high-strength low-dielectric microwave dielectric ceramic material according to claim 1, characterized in that: The relative density of the microwave dielectric ceramic material is 98-99.5%; The dielectric constant of the microwave dielectric ceramic material is adjustable between 6.5 and 8.5, and the dielectric loss is less than 0.001; The microwave dielectric ceramic material has a thermal expansion coefficient of 5 to 8 ppm / °C and a thermal conductivity of >5 W / m·K; The flexural strength of the microwave dielectric ceramic material is ≥230 MPa, and the Young's modulus is ≥200 GPa.

3. The high-strength low-dielectric microwave dielectric ceramic material according to claim 1, characterized in that: The sintering aid comprises high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 glass-ceramics powder, and the added amount of high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 glass-ceramics powder does not exceed 10wt% of the total mass of the raw materials.

4. The high-strength low-dielectric microwave dielectric ceramic material according to claim 1, characterized in that: The SiO2 ceramic powder is SiO2 powder with a particle size of 0.2 to 5 μm.

5. The high-strength low-dielectric microwave dielectric ceramic material according to claim 3, characterized in that: The composition of the high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 glass-ceramics is aLn2O3-bRO-cSiO2-dB2O3-eAl2O3, wherein Ln=Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Cd, Tb, Dy, Ho, Er, Tm, Yb, Lu, R=Ca, Ba, Sr, a=0~10, b=10~30, c=25~50, d=0~5, e=10~30, and a+b+c+d+e=1.

6. The high-strength low-dielectric microwave dielectric ceramic material according to claim 5, characterized in that: The crystalline phases precipitated in the high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 glass-ceramics include one or more of mullite phase, barium silicate phase and calcium silicate phase; wherein the barium silicate phase is BaSiO3 or BaSi2O5; and the calcium silicate phase is CaSiO3 or / and CaSi2O5; The particle size of the high melting point Ln2O3-RO-SiO2-B2O3-Al2O3 glass-ceramic powder is D 90 <2μm.

7. The high-strength low-dielectric microwave dielectric ceramic material according to any one of claims 1 to 3, characterized in that: The sintering aid further comprises a second aid powder; the second aid powder comprises at least one of MgO, Y2O3, ZrO2, AlF3, and CaF2, and the amount of the second aid added does not exceed 5wt% of the total mass of the raw materials; the particle size D of the second aid powder is 90 <2μm.

8. A method for preparing a high-strength low-dielectric microwave dielectric ceramic material as claimed in any one of claims 1 to 7, characterized in that: The steps include: (1) Al2O3 ceramic powder, SiO2 ceramic powder, sintering aid, and solvent are mixed, and then a binder, a dispersant, and a plasticizer are added to obtain a mixed slurry; (2) filtering and vacuum degassing the obtained mixed slurry, and then performing tape casting using a tape casting device to obtain a raw tape; (3) The obtained raw tape is cut and stacked, and then hot isostatically pressed and in-situ sintered to obtain a high-strength, low-dielectric microwave dielectric ceramic material.

9. The preparation method according to claim 8, characterized in that: The viscosity of the mixed slurry is 4-8 KPa·s; the drying temperature of the casting equipment is set at 40-60°C.

10. The preparation method according to claim 8 or 9, characterized in that: Before in-situ sintering, the temperature is raised to 250-350°C at a rate of 0.5-2°C / min and kept at that temperature for 2-4 hours, and then raised to 450-550°C at a rate of 0.5-2°C / min and kept at that temperature for 2-4 hours to fully remove organic matter.

Citation Information

Patent Citations

  • Ceramic substrate fired at low temperature

    JP1996283066A